PENGARUH INTERGOVERNMENTAL REVENUE, INDEKS PEMBANGUNAN MANUSIA, KEKAYAAN DAERAH, DAN OPINI AUDIT TERHADAP PENGUNGKAPAN SUKARELA: (STUDI EMPIRIS : PEMERINTAH DAERAH DI PULAU SUMATERA TAHUN 2018) - Novertasya Jessica; Sugi Suhartono (Jurnal Akuntansi, 2020)
Voluntary disclosure is a disclosure made by the company outside the matters required by the accounting standards set. Voluntary disclosure on local government websites to the public is still very lacking. The sample of the study consisted of 134 local government websites on the island of Sumatra in the year 2018. The objective of this research is to determine the effect of Intergovernmental Revenue, Human Development Index, regional wealth, and Audit opinion on voluntary disclosure. The data analysis techniques used in this study are classical assumption test, descriptive statistical test, F test, t test, and coefficient of determination test by using SPSS 20.0. The source of the company's data is obtained from www.bps.go.id. The results of the F test with a 0.007 result of the < 0.05 stated that intergovernmental revenue, Human Development index, regional wealth, and audit opinions simultaneously have an effect on voluntary disclosure indices. The result of a coefficient of determination test explains that all variables are able to explain the variation of the voluntary Disclosure index by 10.2%. The results showed that the human development index and the audit opinion were positively effect in voluntary disclosure. While the Intergovernmental Revenue and wealth areas are negatively effect in voluntary disclosure. Keywords: Voluntary disclosure, Intergovernmental Revenue, Human Development Index, regional wealth, Audit opinion